A Reforma da Educação Profissionalizante no Brasil (1995-2002): O Caso CEFET-BA - Ribeiro, Ricardo Torres (2008)
This work analyses the Professional Education Reform in Brazil and Implantation of the National Curriculum Directress for the Professional Education in the Centro Federal de Educação Tecnológica da Bahia (CEFET-BA) ambit, in the period of 1995 to 2002, in Building Technicist Course, in the area of Building and Means of Hostess Technicist in the area of Tourism and Hostess, in Salvador city. It is a Subject Matter within an investigative perspective and qualitative exploration. This work reaffirms as essential element the understanding of capitalist system. Elucidate the relation between education and social reproduction in this system. Identify several concepts of competence, discern these notions as main structure of this Reform. In the formal aspect of the course plane analyzed, there was an acceptance of references of the Professional Education Reform in CEFET-BA. In the teachers' knowledge, the competences are not developed in full and universal form, as it is foreseen by teorical references of the Reform. It is stated that there was an accommodation in relation to the standard of competence, because the large majority, 70,6% of total 17 questionnaires applied, showed extreme difficult in connecting the competences, due to the impositive circumstances of changes, the lack of an executable plan and systematized discussions in Salvador's Unit of Teaching.